Assessing the level of reflective practice and critical thinking disposition among nurses in Malaysia - Atan, Ashikin; Abdul Razak, Muhammad Syafiq Afham; Mohd Fadzil, Suhaiza; Azmi, Barkhis; Ruslan, Rusila (UPM Press, 2024)
Introduction: Reflective practice and critical thinking have become essential skills among nurses, as they face various challenges in their daily tasks. These skills help them to maintain high-quality nursing care in a dynamic healthcare system. In particular, reflective practice aids nurses to self-educate and stay motivated throughout the rough days in the hospital, whereas critical thinking among nurses improves their decision-making and problem-solving skills during those difficult situations. Thus, reflective practice and critical thinking among nurses are important for a safer healthcare environment and better overall quality of care. This study aimed to investigate reflective practice and critical thinking dispositions among nurses in Malaysia. Materials and methods: A cross-sectional descriptive study was conducted in one of the teaching hospitals in Malaysia using convenience sampling on 218 participants from different disciplines. The data was analysed using IBM SPSS Statistic 25. Results: Sociodemographic characteristics, including gender, education level, working experience, and working area, did not display statistically significant associations with either reflective practice or critical thinking disposition. Nonetheless, this study found that there was a moderate positive correlation between reflective practice and critical thinking disposition. Conclusion: The finding highlights that nurses engaging in reflective practice tend to exhibit a heightened inclination toward critical thinking. Thus, reflective practice should be further prioritised in the Malaysia nursing curriculum and professional development programmes by adopting appropriate and structured reflective practice frameworks to further cultivate critical thinking among nurses.